Status Gizi, Asupan Makanan dan Status Anemia dengan Kejadian Kekurangan Energi Kronis (KEK) pada Remaja Putri - Sari, Diesna; Annisa, Nurul; Awaru, Andi Fatwa Tenri (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
This study aims to analyze the relationship between nutritional status, food intake, and anemia status with the incidence of Chronic Energy Deficiency (CED) in adolescent girls. The approach used a cross-sectional design involving 58 female students of SMP Negeri 1 Campalagian. Data were collected through anthropometric measurements, hemoglobin level examinations, and 24-hour recall interviews for food intake. Data analysis was performed using the chi-square test. The results of this study indicate that 75.9% of respondents experienced CED. Nutritional status and fat intake are important factors in the prevention of CED in adolescent girls.